Produksi Minuman Kesehatan Teh Uirame di Kampung Koya Tengah, Distrik Muara Tami, Jayapura - Andre M. Worabai; Dimas A. Syafrudin; Fadil M. Al Ridha; Karlin Mansumber; Khoirul Huda; Kristina I. Rahail; Marselina E. Koten; Muhammad M. Khalil; Ota M. Rumainum; Pitera Wenda; Qonita A. Nisa; Sarhana R.A. Said; Yuliana R. Yabansabra; Tatang Sutarman; Elsye Gunawan (Bakti Hayati: Jurnal Pengabdian Indonesia, 2022)
Koya Tengah is one of the villages in Muara Tami District, Jayapura City. KKN organized by Faculty of Mathematics and Natural Sciences, Cenderawasih University took the theme â€œPapua Tangguhâ€. Which aims to contribute to build Papuan community into a resilient community in the health sector. KKN participants provide program about the benefits of spices that are around that can be used to make herbal product â€œUirame Teaâ€ that are useful for increase body immunity. Uirame Tea is made from a mixture of various herbal plants from leaves, twigs, and wood shavings. Herbal plants with many benefits can be processed into a health food or beverage product such as Uirame Tea which needs to be developed because the composition come from spices with antioxidant content. Therefore, in the implementation of Thematic KKN Papua Tangguh, there will be socialization about the benefits and ways of making Uirame Tea to the community, with the aim of understanding the efficacy of uirame tea spice ingredients and knowing how to make Uirame Tea traditionally. This program is carried out for 21 days starting from August 16 to September 5, 2021.Keyword: Uirame tea; Koya Tengah village; PapuaÂ